Benin : Fifth Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
Following satisfactory economic and financial performance under the Poverty Reduction and Growth Facility-supported program, performance was mixed. Benin should pursue a prudent debt-management policy with the support of the newly created debt committee. Implementation of the structural reform agenda is of critical importance for achieving the objectives of the Poverty Reduction Strategy Paper. Strengthening of the financial sector and maintaining external debt on a sustainable path is needed in Benin. Risks to the medium-term program remain, but they are manageable.